Preparation of Reducing Sugar Hydrolyzed from High-Lignin Coconut Coir Dust Pretreated by the Recycled Ionic Liquid [mmim][dmp] and Combination with Alkaline - Hanny F. Sangian; Junaidi Kristian; Sukmawati Rahma; Hellen Kartika Dewi; Debra Arlin Puspasari; Silvya Yusnica Agnesty; Setiyo Gunawan; Arief Widjaja (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
This study aims to produce reducing sugar hydrolyzed from substrate, coconut coir dust pretreated by recycled ionic liquid and its combination with alkaline. The 1H NMR and FTIR were performed to ver-ify the synthesized ionic liquid methylmethylimidazolium dimethyl phosphate ([mmim][dmp]). The structure of pretreated substrates was analyzed by XRD measurement. The used ionic liquid was recy-cled twice to re-employ for substrate pretreatment. The treated- and untreated-coconut coir dust were hydrolyzed into sugars using pure cellulase. The reaction, which called an enzymatic hydrolysis, was conducted at 60 °C, pH 3, for 48 h. The yields of sugar hydrolyzed from fresh IL-pretreated, 1R*IL-pretreated and 2R*IL-pretreated substrates were of 0.19, 0.15 and 0.15 g sugar / g cellu-lose+hemicellulose, respectively. Pretreatment with NaOH or the combination of NaOH+IL resulted in yields of reducing sugars of 0.25, 0.28 g/g, respectively. When alkaline combined with the recycled ionic liquids, NaOH+1R*IL, NaOH+2R*IL in the pretreatment, the yields of sugar were relatively similar to those obtained using alkaline followed by fresh ionic liquid. If the mixture enzymes, cellu-lase+xylanase, used to liberate sugars from fresh IL-pretreated, or recycled IL-pretreated substrates, the amount of sugar (concentration or yield) increased slightly compared to that employing a single cel-lulase. These findings showed that recycled IL pretreatment of the high-lignin lignocellulose, coconut coir dust, is a new prospect for the economical manufacture of fermentable sugars and biofuel in the coming years. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)